International debt shifting: Do multinationals shift internal or external debt? - Jarle Møen; Dirk Schindler; Guttorm Schjelderup; Julia Tropina (Center for Economic Studies and ifo Institute (CESifo), 2011)
Multinational companies can exploit the tax advantage of debt more aggressively than national companies by shifting debt from affiliates in low tax countries to affiliates in high tax countries. Previous papers have either omitted internal debt or external debt from the analysis. We are the first to model the companies' choice between internal and external debt shifting and show that it is optimal for them to use both types of debt to save taxes. Using a large panel of German multinationals, we find strong empirical support for our model. The estimated coefficients suggest that internal and external debt shifting are of about equal relevance. Since the tax variables that determine the incentive to shift internal and external debt are correlated both with each other and with the host country tax rate, previous estimates of the tax sensitivity of debt suffer from omitted variable bias.
Keywords: H25; G32; F23; 330; corporate taxation; multinationals; capital structure; international debt-shifting; tax avoidance; Multinationales Unternehmen; Unternehmensbesteuerung; Steuervermeidung; Fremdkapital; Kapitalstruktur; Deutschland